Greater freedom of speech on Web 2.0 correlates with dominance of views linking vaccines to autism. Issue 12 (17th March 2015) - Venkatraman, Anand; Garg, Neetika; Kumar, Nilay
Abstract Introduction It is suspected that Web 2.0 web sites, with a lot of user-generated content, often support viewpoints that link autism to vaccines. Methods We assessed the prevalence of the views supporting a link between vaccines and autism online by comparing YouTube, Google and Wikipedia with PubMed. Freedom of speech is highest on YouTube and progressively decreases for the others. Results Support for a link between vaccines and autism is most prominent on YouTube, followed by Google search results. It is far lower on Wikipedia and PubMed. Anti-vaccine activists use scientific arguments, certified physicians and official-sounding titles to gain credibility, while also leaning on celebrity endorsement and personalized stories. Conclusions Online communities with greater freedom of speech lead to a dominance of anti-vaccine voices. Moderation of content by editors can offer balance between free expression and factual accuracy. Health communicators and medical institutions need to step up their activity on the Internet.